PENINGKATAN KEMAMPUAN MENGAJAR GURU MELALUI KEGIATAN SUPERVISI DI SMP NEGERI 1 KAMPAR TIMUR KABUPATEN KAMPAR - Mulhadi Mulhadi (Jurnal PAJAR (Pendidikan dan Pengajaran), 2018)
This study aims to determine whether the supervision activities to improve teachers' teaching skills in SMP Negeri 1 Kampar Timur, Kampar. Based on background description, problem identification and problem restriction, the focus of this research is related to supervision activities to improve teachers' teaching abilities in SMP Negeri 1 Kampar Timur, Kampar. The School Action Research is conducted only at SMP Negeri 1 Kampar Timur Kampar District. In one supervision of the researcher himself. The type of this research is School Action Research (PTS) located in SMP Negeri 1 Kampar Timur, Kampar, which is aimed at teachers. The main reason is from the results of observation and information from teachers, that pedagogic competence of teachers is still classified as less. The sample in this study is all teachers in SMP Negeri 1 Kampar Timur, Kampar amounted to 55 people. From the description of data processing and discussion, it can be concluded that the pedagogic competence of teachers obtained in the first cycle of 60% with good category and on the second cycle increased to 80% with good category. This means that supervision activities can improve teachers' teaching skills in SMP Negeri 1 Kampar Timur, Kampar is said to succeed.